Steroidogenic control of liver metabolism through a nuclear receptor-network - Alexandra Milona; Vittoria Massafra; Harmjan Vos; Jyoti Naik; Natalia Artigas; Helen A.B. Paterson; Ingrid T.G.W. Bijsmans; Ellen C.L. Willemsen; Jose M. Ramos Pittol; Irene Miguel-Aliaga; Piter Bosma; Boudewijn M.T. Burgering; et al. (Elsevier, 2019)
Objective: Coupling metabolic and reproductive pathways is essential for the survival of species. However, the functions of steroidogenic enzymes expressed in metabolic tissues are largely unknown. Methods and results: Here, we show that in the liver, the classical steroidogenic enzyme Cyp17a1 forms an essential nexus for glucose and ketone metabolism during feed-fast cycles. Both gain- and loss-of-function approaches are used to show that hepatic Cyp17a1 is induced by fasting, catalyzes the production of at least one hormone-ligand (DHEA) for the nuclear receptor PPARα, and is ultimately required for maintaining euglycemia and ketogenesis during nutrient deprivation. The feedback-loop that terminates Cyp17a1-PPARα activity, and re-establishes anabolic liver metabolism during re-feeding is mapped to postprandial bile acid-signaling, involving the receptors FXR, SHP and LRH-1. Conclusions: Together, these findings represent a novel paradigm of homeostatic control in which nutritional cues feed-forward on to metabolic pathways by influencing extragonadal steroidogenesis. Keywords: FXR, FGF21, Bile acids, Liver, Metabolism, Fasting, Gluconeogenesis, Diabetes, Steroidogenesis, Cyp17a1